1992
DOI: 10.1021/jf00022a017
|View full text |Cite
|
Sign up to set email alerts
|

Determination of conjugated linoleic acid content and isomer distribution in three Cheddar-type cheeses: effects of cheese cultures, processing, and aging

Abstract: Conjugated linoleic acid (CLA) is a mixture of positional and geometric isomers of linoleic acid with conjugated double bonds. Several investigators have suggested that CLA has anticarcinogenic properties. This study describes the quantification of CLA isomers in three Cheddar-type cheeses relative to the effects of different cheese cultures, processing conditions, and aging periods. An improved method was developed for quantifying CLA isomers in cheese such that isomerization did not occur. Three 13month-aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
101
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 14 publications
(40 reference statements)
12
101
0
3
Order By: Relevance
“…In contrast, others have described that the period of ripening does not alter CLA contents (Werner 1992;Luna et al 2007), because, on one hand, a longer time for the bacteria to act involves an increase in the CLA contents, whereas, on the other, oxidising reactions could lead to the destruction of the double bonds, thus decreasing CLA levels (Lin et al 1995;Domagala et al 2010).…”
Section: Resultsmentioning
confidence: 91%
“…In contrast, others have described that the period of ripening does not alter CLA contents (Werner 1992;Luna et al 2007), because, on one hand, a longer time for the bacteria to act involves an increase in the CLA contents, whereas, on the other, oxidising reactions could lead to the destruction of the double bonds, thus decreasing CLA levels (Lin et al 1995;Domagala et al 2010).…”
Section: Resultsmentioning
confidence: 91%
“…54,57 It has been reported that CLA exhibits conversion from c, t or t, c isomers to t, t isomers or unknown substances as a consequence of BF 3 methylation. 38 The use of the milder BCl 3 -methanol reagent in place of the BF 3 -methanol reagent has similar results. 54 …”
Section: Acid-catalysed Methods (Fig 1)mentioning
confidence: 81%
“…57,61,62 Lowering the methylation temperature can decrease CLA isomerization, but these milder conditions may not be sufficient to methylate all lipids. 38,60,63 …”
Section: Hydrochloric Acid (Hcl) In Methanolmentioning
confidence: 99%
See 1 more Smart Citation
“…Also Ha et al [26] and Prandini et al [63] reported higher CLA contents in the fat of cheese than in the fat of milk. Werner et al [82], Jiang et al [29], Gnädig et al [22], Nudda et al [54] and Ryhänen et al [73] observed no significant effect of processing on the CLA content in cheese, including blue cheese, Edam cheese, Swedish Swisstype cheese, French Emmental and other hard cheeses, and Pecorino Romano cheese and Ricotta cheese made from the corresponding sheep's milk. Gnädig et al [22] investigated different processing factors such as raw or mildly heated milk (68 °C/20 s), cooking/moulding temperatures of 52 °C/50 °C or 48 °C/48 °C or 50 °C/ 50°C and different strains of Propionibacterium freundenreichii, and found no effect on CLA content in French Emmental cheese.…”
Section: Effects Of the Cheesemaking Processmentioning
confidence: 99%